Advancing a theory of change in a collaborative teacher education program innovation through universal design for learning. Issue 1 (2023) - Mackey, M.; Drew, S.V.; Nicoll-Senft, J.; Jacobson, L.
Abstract: This design-based research (DBR) investigates the redesign of a 13-month interdisciplinary teacher preparation program to co-prepare secondary and special education teacher candidates to plan and implement evidence-based practices to meet content and literacy needs of all learners within secondary classrooms. The Theory of Change explores mechanisms for change under the umbrella of Universal Design for Learning (UDL). The UDL framework can support teacher candidates in meeting the needs of students with exceptionalities in the general education classroom, yet few studies have explored the in-depth application of UDL in authentic settings across preparation program duration. DBR methods organize study design, iterative data collection, and retrospective analysis of artifacts including candidates' edTPA portfolios and action research papers. Findings revealed strengths and challenges in candidates' ( n = 14) application of components. Results for specific components and various disciplines are discussed. Implications for collaborative preparation of general and special education candidates are identified.